ANALISIS BAHASA POLITIK ANIES BASWEDAN DALAM PIDATO PENGUKUHANNYA SEBAGAI GUBERNUR JAKARTA PERIODE 2017-2022 - Dhea Tisane Ardhan (Department of Master of Linguistic, Universitas Airlangga, 2020)
Related to the political aspect, language selection becomes a crucial element for the perpetrators. Political language can be considered to have a